IDENTIFIKASI KESULITAN BELAJAR ONLINE DI MASA PANDEMI COVID-19: STUDI KASUS PADA MAHASISWA PGSD - Mutiara Salsabila Awani; Eddy Noviana; Eva Astuti Mulyani (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
The emergence of the COVID-19 disease worldwide including in Indonesia, the coronavirus is a respiratory disease that attacks humans beginning from the common flu to quite serious illnesses. It causes a huge impact on various fields in Indonesia, especially in the field of education where learning is implemented online consequently. Although it was easy to implement this online learning system, in fact, there are still many students who have difficulty implementing this online learning. The study described in this article is designed to find out what difficulties were experienced by PGSD students during the online learning processes. Type of study used was qualitative research. The data sources of the study were derived from 36 students in the class of the year 2019. The results indicated that the difficulties experienced by PGSD students were derived from a dislike of learning online, playing on social media and not paying attention to the lecturers or friends in explaining the material provided in class, feeling bored in the online learning process, unable to understand the material given by the lecturer, the improvement in learning outcomes but not with full understanding, and network constraints during the online learning processes.